Outcome of pulmonary sarcoidosis: a population-based study 1976-2013 - Ungprasert, Patompong; Crowson, Cytnthia S; Carmona, Eva M; Matteson, Eric L (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: A hallmark of sarcoidosis is lung disease. However, the prognosis and long-term outcome of pulmonary sarcoidosis are not well-defined due to the limited number of studies with long duration of follow-up. Objectives: This study was undertaken to characterize the course of pulmonary sarcoidosis in a population-based cohort. Methods: A population-based cohort of 311 incident cases of pulmonary sarcoidosis among Olmsted County, Minnesota residents in 1976-2013 were identified. Medical records of the confirmed cases were reviewed from diagnosis to last follow-up.  Data on stage of pulmonary sarcoidosis at diagnosis, serial pulmonary function tests, requirement of oxygen therapy and treatment were abstracted. The cumulative incidence of chronic respiratory impairment (defined as forced vital capacity of